2015
DOI: 10.1007/s12011-015-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Selenium from Hydroponically Produced Selenium-Enriched Kale Sprout (Brassica oleracea var. alboglabra L.) in Broilers

Abstract: An experiment was conducted to determine the efficacy of Se from hydroponically produced Se-enriched kale sprout (HPSeKS) on performance, carcass characteristics, tissue Se concentration, and physiological responses of broilers in comparison to that of Se from Se-enriched yeast and sodium selenite. Three hundred and sixty male broilers, 10 days of age, were assigned to 6 groups, 4 replicates of 15 broilers each, according to the completely randomized design. The dietary treatments were the following: T1: contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…erefore, the amount of Se in Se-KS did not exceed the toxicity doses reported; for this reason, no signs of toxicity in animals were seen in the present experiment. Indeed, together with our previous research [18][19][20], good biological activity was proven for the Se-KS with low acute toxicity when compared with selenite. We suggest 0.05-0.15 g of the air-dried Se-KS corresponded with 0.025-0.065 mg Se per day [6] or a maximum dose of <0.7 g of the air-dried Se-KS corresponded with a tolerable dose 0.3 mg Se per adult and day [7].…”
Section: Acute Toxicity Study In Ratsmentioning
confidence: 67%
See 1 more Smart Citation
“…erefore, the amount of Se in Se-KS did not exceed the toxicity doses reported; for this reason, no signs of toxicity in animals were seen in the present experiment. Indeed, together with our previous research [18][19][20], good biological activity was proven for the Se-KS with low acute toxicity when compared with selenite. We suggest 0.05-0.15 g of the air-dried Se-KS corresponded with 0.025-0.065 mg Se per day [6] or a maximum dose of <0.7 g of the air-dried Se-KS corresponded with a tolerable dose 0.3 mg Se per adult and day [7].…”
Section: Acute Toxicity Study In Ratsmentioning
confidence: 67%
“…Moreover, Se-Met and MSeCys were the major organic forms of Se-enriched Chinese kale seedlings [18]. e bioavailability of Se from Se-enriched Chinese kale seedlings (Se-KS) is similar to that of Se-enriched yeast but higher than that of Se from sodium selenite in broilers [19] and laying hens [20]. Furthermore, the toxicity of Se from Se-KS was studied in laying hens, and it showed less toxicity than Se from sodium selenite at 5 and 10 mg•Se/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Chantiratikul et al [10] similarly found no impact of dietary Se supplementation form SeKS (0.2 to 1.0 mg/kg) on feed intake, performance, and carcass characteristics of quails. Trials in broilers also reported that Se sources from SS, SeY, SeKS, 2-hydroxy-4-methylselnobutanoic acid, and SeMet at 0.1 to 2.0 mg/kg diet did not alter feed intake and growth performance parameters [2,5], and carcass traits [13]. The Se concentration in the control diet was 0.25 mg/kg (Table 2), which met the Se requirement for quail (0.15 mg Se/kg) recommended by NRC [18].…”
Section: Discussionmentioning
confidence: 95%
“…Species of Se in SeKS were mostly present as organic forms [11]. The scientific reports found that the efficacy of Se from SeKS and SeY was comparable, but greater than that of Se from SS in laying quails [12], broilers [13], and laying hens [14]. Furthermore, Se from SeKS has been confirmed to be less toxic in laying hens [15] and in rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…El Se es un elemento traza esencial que se encuentra principalmente como Se inorgánico (muchas veces como selenito o selenato) y Se orgánico en forma de selenometionina, el cual, en esta forma, es mayormente asimilable (Chantiratikul, et al, 2015). El Se tiene una ingesta diaria recomendada (IDR) de 60 µg por día para hombres y de 53 µg por día para las mujeres (Rayman, 2012).…”
Section: Seleniounclassified